Transfection, expression, and dna-Sequence of a gene encoding a Bola-A11 antigen - Sawhney, S.M.S.; Hasima, N.N.; Glass, E.J.; Almurrani, S.W.K.; Nichani, A.K.; Spooner, R.L.; Williams, J.L.; Russell, G.C. (1995)
Cattle major histocompatibility complex (MHC) (BoLA) class I molecules are heterodimeric glycoproteins which present endogenous antigenic peptides to CD8{sup +} T lymphocytes, initiating a cellular immune response. The MHC-encoded heavy chains are highly polymorphic and, in cattle, have been characterized mainly by using allo-antisera raised by reciprocal calf/dam immunizations. This has enabled the identification of about 50 serlogical specificities, most of which behave as alleles of a single highly polymorphic class I locus. However, evidence from biochemical and molecular biological studies suggest that more than one BoLA class I locus is expressed. These loci are apparently in linkage disequilibrium, making them difficult to distinguish by conventional methods. In order to investigate the expression and function of individual class I locus products, we are correlating BoLA class I gene sequences with the expressed products by the transfection and characterization of genomic class I clones. Shotgun transfection and expression of BoLA class I molecules has been described previously, but the genes involved were not isolated. In this paper we report the isolation, DNA sequencing, transfection, and expression of a genomic clone encoding a BoLA-A11 determinant from an animal expressing A10 and A11 serological specificities. 23 refs., 3 figs.